Strategi Efektif Guru PAI Dalam Mengatasi Kesulitan Membaca Al-Qur’an: Studi Kasus di SMA Nurul Yaqin Tanjung Batu - Siti Baina Haliza; Rozikin; Ahmad Abdul Qiso (TAUJIH: Jurnal Pendidikan Islam, 2024)
This research aims to identify the efforts of Islamic Religious Education teachers in overcoming students' difficulties in learning to read the Al-Qur'an at Nurul Yaqin High School as well as supporting and inhibiting factors that help teachers overcome these challenges. Descriptive qualitative field research was used. Data sources are primary and secondary; data collection techniques are observation, interviews, and documentation; checking the validity of the data is carried out by triangulating sources, methods and time; and data analysis is reduction, presentation, and verification. The results show that PAI teachers try to overcome difficulties in learning to read the Al-Qur'an by providing motivation, studying the Al-Qur'an 30 minutes before class time, studying the Al-Qur'an in groups, and collaborating with other subject teachers. Factors that support teachers in overcoming difficulties in learning to read the Al-Qur'an are: (1) support from the school; (2) available facilities and infrastructure, and (3) religious activities. Meanwhile, the factors that hinder it are: (1) often reading the letters of the Koran incorrectly; (2) how to apply recitation of the Koran; (3) how to say hijaiyah letters; (4) difficult to understand recitation; (5) looking for free time to study the Koran. The results of this research show that PAI teachers have a very important role in overcoming students' difficulties in reading the Koran, therefore PAI teachers must really maximize their role in learning at school.